O lúdico e as multimeioses: ensino de leitura e de escrita na perspectiva de alfabetizar letrando no 2º ano do ensino fundamental - Silva, Raquel Paula da (2023)
We are distressed by the difficult reality of education in our country, especially in these last 2(two) years with the spread of the covid-19 pandemic. However, despite realizing that neglect of education has intensified with the pandemic, we recognize that this is na old problem, especially with regard to the alphabetization process. Analyze how educational games based on ludicity and multi semiosis can contribute to the alphabetization process in a literacy context. In that regard, we will seek to stimulate the reading and writing process, in the 2nd year of Elementary School, through ludic and its multi semiosis. Furthermore, we will address each process – Reading and Writing, Alphabetization and Literacy, Multi semiosis and Ludicity – showing is concepts, characteristics and particularities. For the construction of this work, a methodology of a descriptive and propositional nature was used, employing a bibliographic research procedure, and a qualitative approach. Therefore, our theoretical foundation is based on the perspectives os some scholars, for example: Almeida (2013/ 2014), Andrade and Silva (2015), Cunha (2013), Diniz (2018), França (2016), Kleiman (2005), Morais (2012), Rojo (2010), Leite and Colello (2010), Lopes (2015), Morais (2012), Mineiro and D’Ávila (2019), Nöth (2013), Pignatari (2004), Soares (2021), among others. Therefore, the contributions of official documents: Child and Adolescent Statute (ECA – Estatuto da Criança e do Adolescente, 1990), Law Guidelines and Bases of National Curriculum (LDB – Lei de diretrizes e Bases da educação Nacional, 1996), National Curriculum Parameters (PCN – Parâmetros Curriculares Nacionais, 1998), Common National Curriculum Bases (BNCC – Base Nacional Comum Curricular, 2017), as well as the Linguistics Dictionaries (2006) and the Minidictionary of the Portuguese Language by Evanildo Bechara (2009). Before long, considering the studies we carried out on the reading and writing process of students enrolled in the 2nd year of Elementary School, we understand that the multi semiosis that appear in pedagogical games can provide a better development of children’s language skills. We found, from the theoretical and methodological discussions, that pedagogical games linked to multi semiosis are didactic-pedagogical tools that contribute positively to the acquisition of reading and writing skills by students in the 2nd year os Elementary School.